P083 The transcriptomic signature of IL-23-treated lamina propria mononuclear cells is significantly enriched for genes in the Th17 pathway and is enriched in active UC. (25th January 2019) - Digby-Bell, J; Pavlidis, P; Niazi, U; Kassam, Z; Prescott, N; Perucha, E; Saqi, M; Powell, N
Abstract: Background: Subunits of interleukin-23 (IL-23) and its receptor have been identified as susceptibility genes in genome-wide association studies (GWAs) in ulcerative colitis (UC). Moreover, functional pre-clinical studies have shown that IL-23 is a key cytokine in the pathogenesis of UC. Here, we define an IL-23-induced transcriptomic signature in lamina propria mononuclear cells (LPMCs). We hypothesised that this signature would be enriched in active UC (aUC) compared with inactive UC (iUC) and healthy controls (HC), and enriched in anti-TNFα non-responders compared with anti-TNFα responders. Methods: LPMCs were isolated from colonic biopsies obtained endoscopically from 5 aUC and cultured in the presence or absence of IL-23 for 4 h. Cells were lysed, RNA was extracted and RNA sequencing performed using the Illumina platform. Analysis of differentially expressed genes (DEGs) was performed between the untreated and IL-23 treated LPMCs using DESeq2, filtered with p < 0.01 and examined for enrichment in biological pathways using Ingenuity Pathway Analysis (IPA). To assess association of the transcriptomic signature to clinical phenotypes, Gene Set Variation Analysis (GSVA) enrichment scores were calculated in open access data sets of microarray data of colonic biopsies from HC and UC including the ACT1 trial (GSE16879 HC = 6, UC = 24; GSE57091 HC = 11, iUC = 23, aUC = 74; GSE23597 anti-TNFα responders = 2, non-responders = 7). Results: In total, 112 DEGs were identified, including IL22, IFNγ and IL17F which are downstream targets IL-23. Canonical pathway analysis of the DEGs demonstrated 'Th17 activation' pathway as the most significantly enhanced. GSVA enrichment scores using the 'LPMC untreated v IL23' signature showed a significantly higher score in UC compared with HC in data set GSE16879 ( p = 0.006). Furthermore, there was significantly greater enrichment in aUC compared with iUC in data set GSE59071 ( p < 0.00001). However, GSVA enrichment scores calculated on colonic biopsies of patients with UC before commencing anti-TNFα therapy did not show a significant difference between anti-TNFα responders and non-responders (dataset GSE16879 p = 0.07; dataset GSE23597 p = 0.1). Conclusions: The herein described IL-23 signature induces an appropriate and expected downstream transcriptional profile. GSVA enrichment scores in open access datasets shows enrichment in aUC compared with both HC and iUC. However, enrichment scores were not significantly different when comparing anti-TNFα responders and non-responders though this may be due to lack of power due to a low sample numbers. Transcriptomic signatures have the potential to act as biomarkers to aid clinical decision making.